Photoluminescence and dielectric properties of pure/Yb-doped SrZrO3 crystals. (May 2017) - Zhang, Lulu; Wang, Jilin; Peng, Daijiang; Long, Fei; Mo, Shuyi; Wu, Yi; Zou, Zhengguang
Abstract: High quality SrZrO3 nanocubes have been successfully synthesized via a facile hydrothermal method using Sr(NO3 )2 and Zr(NO3 )4 ·5H2 O as raw materials. Then, the Yb-doped SrZrO3 were also fabricated by solid state reaction using the as-synthesized pure SrZrO3 . The phase structure, morphology, composition and specific surface area of the samples were investigated by XRD, FESEM, EDS, TEM, FTIR, Raman and BET techniques. The as-synthesized SrZrO3 nanocubes distributed homogeneously and displayed sharp edges with an average particle size of about 100 nm. In addition, the dielectric loss value of the pure SrZrO3 at 1 MHz was only 0.05 when the temperature rose from 25 °C to 550 °C, indicating a good dielectric property at high temperature. Meanwhile, the band gap of SrZrO3 could be reduced by about 0.3 eV after Yb 3+ doping, where Yb 3+ mainly occupied Sr 2+ position (A site doping). Besides, all of the pure and Yb-doped SrZrO3 samples exhibit violet light emission centered at 423 nm (excited at 372 nm), which was originated from material intrinsic defects. Graphical abstract: High quality SrZrO3 nanocubes have been successfully synthesized via a facile hydrothermal method. Then, the Yb-doped SrZrO3 were also fabricated by solid state reaction using the as-synthesized pure SrZrO3 . The as-synthesized SrZrO3 nanocubes distributed homogeneously and displayed sharp edges with an average particle size of about 100 nm. In addition, the dielectric loss value of the pure SrZrO3 at 1 MHz was only 0.05 when the temperature rose from 25 °C to 550 °C. Meanwhile, the band gap of SrZrO3 could be reduced by about 0.3 eV after Yb 3+ doping, where Yb 3+ mainly occupied Sr 2+ position (A site doping). Besides, all of the pure and Yb-doped SrZrO3 samples exhibit violet light emission centered at 423 nm (excited at 372 nm), which was originated from material intrinsic defects. Highlights: Pure/Yb-doped SrZrO3 powders have been synthesized. Tuning the band gap of pure SrZrO3 by doping Yb 3+ ions. The dielectric and photoluminescence properties of SrZrO3 were studied.